Primary Percutaneous Coronary Intervention in ST-Elevation Myocardial Infarction with Acute Kidney injury caused by Cardiogenic Shock, Is it Really Safe?; A Case Report - Oktafin Srywati Pamuna; Mohammad Saifur Rohman; Setyasih Anjarwani; Cholid Tri Tjahjono (Universitas Brawijaya, 2021)
BackgroundST-elevation myocardial infarction (STEMI) is a life-threatening condition. Timely treatment with Percutaneous Coronary Intervention (PCI) is a recommended management of STEMI. However, in STEMI condition accompanied by complications such as prolonged shock condition and become Acute Kidney Injury (AKI), it is still a question of whether to be treated conservatively or invasively. If PPCI was an option, how to prevent the worsening outcome is still an issueCase IllustrationA 53 years old, woman, was referred from a private hospital with STEMI inferior Killip IV onset 5 hours with typical chest pain and azotemia with creatinine serum was 3.4 mg/dl; eGFR 15 ml/m/1.73m2. In the emergency room, she got hydration, inotropic, and planned for PPCI. After the PPCI procedure, she was fallen into the altered mental status and then referred to our hospital. The GCS was E4V4M6; blood pressure was 118/62 mmHg (on dobutamine 10 mcg/kg BW/minutes and NE 0.3 mcg/kg BW/minutes), heart rate was 130 bpm, respiration rate was 20 times per minute, peripheral saturation was 98% on NRBM 10 liters per minute. The laboratorium result in our hospital showed a creatinine level was 1.6 mg/dl. We treated this patient for 9 days, with optimal medicamentosa and fluid therapy. There is an improvement in clinical presentation and physical examination on the last day of treatment, with urine output 1900 cc/24 hours, creatinin serum 0.8 mg/dl, and eGFR 84 ml/min/1.73m2.Conclusion Acute renal failure is a frequent complication in STEMI, leading to higher mortality, morbidity, and intrahospital complications. PPCI is a reperfusion strategy recommended by the guideline in the setting of myocardial infarction with cardiogenic shock. Proper management to prevent worsening of renal function in this condition is very important. Keyword: acute kidney injury, cardiogenic shock, ST-elevation myocardial infarction